Lithium mode of action : a role for cyclic nucleotides and nitric oxide? - Harvey, Brian Herbert (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Medical sciences)) -- University of Stellenbosch, 1992.